A Customized Data Model for an Integrated Process of Requirements and Configuration Management - Oliveira,Sérgio Ricardo de Freitas (2022)
ABSTRACT This work aims to propose a customized, open-source data model for supporting an integrated process of Requirements and Configuration Management that allows for keeping track of which requirement originated each part, subsystem and system—and vice versa—, over their entire life cycle. That model might prospectively contribute to the processes of Aeronautical Engineering design and Continued Airworthiness in organizations that do not want either to invest in complex existing commercial, proprietary software packages or to train their professionals for that purpose. The complete source code of the model is provided in Python and SQL languages.